The Significance of the Traditional Courtyard Components of Shophouses in Georgetown, Penang Malaysia - Zwain, Akram; Bahauddin, Azizi (School of Social Sciences, USM, 2017)
A courtyard is an architectural design component commonly applied in tropical buildings for its social and environmental purpose. The traditional courtyard shophouses in George Town, Penang in Malaysia were influenced by the eastern and western cultures. The city of George Town was added to the UNESCO's world heritage list in 2008 to acknowledge its rich cultural heritage that constitutes of unique architectural and cultural townscape along the Straits of Melaka. In many researches, the style of shophouse (eclectic style) will be called for a building that is greater than hundred years. They are rich in design and art components featured in its architecture that is still surviving until today. This unique type of structure clearly shows the influences of Chinese, Malay, Indian and European styles; matured and merged together in response to the local environment. From the Chinese influence, in the courtyard was introduced. The courtyard is a significant typological element in a shophouse. In George Town, the traditional courtyard shophouses have characteristics that are appropriate for the local region. However, most traditional shophouses faced alterations and deterioration and become a major concern in Penang. In addition, there has been a tendency proven since over thirty years ago of excessive replacement the traditional courtyard houses with multi-storey buildings. All of these have seriously affected the cultural continuity of the traditional shophouses form. This paper employed the qualitative research approach that obtained data from the observation and secondary sources to understand the design of the traditional courtyard architectural components of shophouses. The findings of the research point towards the understanding of the significance of the traditional courtyard, environmental aspect and design variants of shophouses.